Mitochondrial Fission Protein 1: Emerging Roles in Organellar Form and Function in Health and Disease - Ihenacho, Ugochukwu Kelvin; Meacham, Kelsey A.; Harwig, Megan Cleland; Widlansky, Michael E.; Hill, R. Blake (Frontiers in Endocrinology, 2021)
Mitochondrial fission protein 1 (Fis1) was identified in yeast as being essential for mitochondrial division or fission and subsequently determined to mediate human mitochondrial and peroxisomal fission. Yet, its exact functions in humans, especially in regard to mitochondrial fission, remains an enigma as genetic deletion of Fis1 elongates mitochondria in some cell types but not others. Fis1 has also been identified as an important component of apoptotic and mitophagic pathways suggesting the protein may have multiple, essential roles. This review presents current perspectives on the emerging functions of Fis1 and their implications in human health and diseases, with an emphasis on Fis1’s role in both endocrine and neurological disorders.